The Structural Behavior of Indirectly Loaded Flanged Deep Reinforced Concrete Beams - Mohammad-Ali, Anis A.; Laftah, Yousif Jabbar (Basrah Journal for Engineering Sciences, 2010)
The study aimed to investigate the structural behavior of indirectly loaded flanged deep reinforced concrete beams. Twenty-one flanged deep beams were tested. The behavior of beams under loading was observed. Cracking and ultimate loads were recorded.